The time horizon of corporate governance effect on firm performance: a study of Indonesia financial industry firms - Yie Ke Feliana; Ella Rahayu (University of Merdeka Malang, 2022)
Corporate governance is still an important issue today because poor governance can be the cause of business failure. Therefore, good governance is needed to maintain business sustainability. This study aims to examine and analyze the effect of corporate governance, namely the board of commissioners, audit committee, and risk monitoring committee on the company's current and long-term performance. In addition, the corporate secretary is added as a variable that moderates the influence of the board of commissioners on firm performance. The object of research is financial firms listed on the IDX in 2017-2020. This study found that a qualified corporate secretary can positively moderate the proportion of independent commissioners on the company's current and long-term performance. Audit committee qualifications have a significant positive effect on current and long-term performance. The meeting of the risk monitoring committee has no effect on the firm's performance for the current year but has a significant positive effect on the firm's long-term performance. Considering these results, this study suggests that companies should implement good governance today because it has an impact on firm performance in the future.